A New Approach in Synthesis of Some Telluro Compounds - Rani, Rekha; Ranjan, Rajeeva; Kumar, Ashutosh; Sharma, Navin; Sharma, S. (Asian Journal of Chemistry, 2010)
Aryl mercuric chloride (ArHgCl) undergoes transmetallation reaction with aryl tellurium chloride (ArTeCl3) to form diaryl tellurium chloride (Ar-TeCl2-Ar). This compound on further reduction forms diaryl telluroether or diaryl telluride. This compound may also be formed by the addition of tellurium powder to phenyl magnesium iodide in THF, followed by vigorous stirring. This method, however is not suitable when phenyl group bears substituent like NH2 or NHR or NR2 group. But the above transmetallation reaction helps to form the various diaryl telluro compounds having various substitution on aryl rings. On the basis of IR and NMR spectral study, the geometry around Te in Ar2TeCl2 is found to be trigonal bipyramidal with two chlorine occupying the axial positions and two aryl group occupying the two equatorial point while the only lone pair occupies one of the corners of the triangle.